Effects of intellectual at Ibn bajeh )475-533 A.H 1082-1138 A.D) - sarem, wafaa; warda , zainab; hamdosh , Mahmoud (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Ibn bajeh knew sergistias as the last philosophers of islam in Andalusia . he was also the father of rational philosophy . where differentiate mentality tendency in his understanding of science and philosophical. But in addition to politics , he was awriter and minister in the marabit court . he was also worked in various fields of natural sciences, astronomy , mathematics , medicine and music . he had many works of great intellectual and cultural influence and based on his views and ideas many scientists and philosophers in the east and west . there fore , we saw it is important to highlight the role played by this thinker in the cultural and intellectual life of his time and his intellectual production , which was reported by contemporary scientists and later .